Vestibular Migraine I: Mechanisms, Diagnosis, and Clinical Features - Baloh, Robert W. (Seminars in Neurology, 2020)
Vestibular migraine (VM), also known as migrainous vertigo or migraine-associated vertigo, is characterized by recurrent vestibular attacks often accompanied by migraine headaches and other migraine symptoms. It is one of the most common presenting complaints to physicians in primary care, otolaryngology, and neurology. Epidemiologic data suggest that VM may affect 1 to 3% of the general population and 10 to 30% of patients seeking treatment for dizziness. Attacks typically last minutes to hours and range from spontaneous and positional vertigo to extreme sensitivity to self and surround motion. As with headaches, nausea, and vomiting, phonophobia and photophobia are common accompanying symptoms. The clinical spectrum of VM and its underlying pathophysiological mechanisms are just being identified, with much debate about the causal relationship of vestibular symptoms and headache, no evidence-based guidelines for clinical management, limited characterization of its disease burden, and little information about its negative impact on health-related quality of life.
Keywords: vestibular migraine; vertigo; dizziness; aura; spreading depression